Literatura e Política: a dramaturgia shakespeariana e o humanismo na Inglaterra - Loureiro, Cinthya Luciano (2019)
The historical context which William Shakespeare lived (1564-1616) was marked by political, religious and cultural changes during the reigns of Elizabeth I (1558-1603) and Jaime I (1603-1625). England at this time still had some medieval remnants and was